2020
DOI: 10.1111/zph.12702
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii in wild boar and deer in Brandenburg, Germany

Abstract: Consumption of game in Germany has increased during the past 10 years. Wild boar (Sus scrofa), roe deer (Capreolus capreolus) and red deer (Cervus elaphus) are the most frequently hunted and consumed game animals in Germany, yet information on the occurrence of zoonotic pathogens in these animal species is scarce. To better estimate the public health risk emanating from handling and consumption of game, this study investigated seroprevalences of Toxoplasma gondii in game hunted in the German federal state of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…These aspects suggest the need to carefully evaluate T. gondii infection in hunted animals for public health protection in the Mediterranean ecosystem, in accordance with Almería et al (2018). To date, several studies have reported T. gondii seropositivity in wild boar populations in Italy (14.0%- Ranucci et al, 2013;12.2%-Papini et al, 2018) and an estimated pooled seroprevalence of 26.0% in Europe (Bier et al, 2020;Rostami et al, 2017). However, little is known about the main route of infection in these wild ungulates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These aspects suggest the need to carefully evaluate T. gondii infection in hunted animals for public health protection in the Mediterranean ecosystem, in accordance with Almería et al (2018). To date, several studies have reported T. gondii seropositivity in wild boar populations in Italy (14.0%- Ranucci et al, 2013;12.2%-Papini et al, 2018) and an estimated pooled seroprevalence of 26.0% in Europe (Bier et al, 2020;Rostami et al, 2017). However, little is known about the main route of infection in these wild ungulates.…”
Section: Discussionmentioning
confidence: 99%
“…(2018). To date, several studies have reported T. gondii seropositivity in wild boar populations in Italy (14.0%—Ranucci et al., 2013; 12.2%—Papini et al., 2018) and an estimated pooled seroprevalence of 26.0% in Europe (Bier et al., 2020; Rostami et al., 2017). However, little is known about the main route of infection in these wild ungulates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown widespread distribution of T. gondii in wild ungulates in Europe, with a high heterogeneity in the presence of the parasite depending on the geographic area and species tested (Bartova et al, 2007;Bier et al, 2020;García-Bocanegra et al, 2012;Gauss et al, 2006;San Miguel et al, 2016;Witkowski et al, 2015). However, few studies have assessed the seroprevalence of this parasite in wild ungulates sharing the same habitat (Bier et al, 2020;Panadero et al, 2010). The aim of the present study was to determine seroprevalence and risk factors associated with T. gondii infection in large game ungulates that cohabit in Sierras de Cazorla, Segura and Las Villas Natural Park (SCSV-NP) (Southern Spain).…”
mentioning
confidence: 99%
“…Animal age was defined by the hunters based on teeth eruption, teeth replacement, and physical appearance (Habermehl 1961;Bier et al 2020). Further, wild boars were divided in three age groups (0, 1, 2).…”
Section: Methodsmentioning
confidence: 99%
“…Wild boars younger than 1 year belong to age group 0 and 1 year old animals are part of age group 1. All wild boars aged 2 years or older belong to age group 2 (Game Management Directive of the German federal states of Brandenburg and Mecklenburg-Western Pomerania 2001; Portier et al 2014;Bier et al 2020).…”
Section: Methodsmentioning
confidence: 99%